Analisis Perbedaan Konsumsi Protein pada Remaja Putri Yang Mengalami KEK Usia 15-19 Tahun di Daerah Pesisir dan Non Pesisir - Dea Ananda Nur Aeni; Dwi Kurnia P.S; Ahmad David Royyifi Arifin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
One of the macronutrients for the prevention of Chronic Energy Deficiency (SEZ) is protein. Muscle mass is affected by the level of adequacy of energy and protein, the level of adequacy of energy and less protein can lead to a decrease in muscle mass in the subject. If protein intake is sufficient, then nutritional status will be good including the size of the upper arm circumference (LILA). Factors that are strongly suspected to influence the diet of protein sources are the type of region that is closely related to the potential of the region in providing natural food for its population. The availability of various foods is largely determined by geographical conditions (including topography) of the region because it will affect the amount and type of food that can be produced by the region. Objective: This study is to determine the difference in protein consumption of adolescent girls who experience SEZ aged 15-19 years in coastal and non-coastal areas. This type of research is an observational analytical design with a comparative study approach with a population of 213 respondents selected by cluster random sampling technique and obtained 138 respondents. Data on independent and dependent variables were collected through questionnaire interview techniques. The Independent Sample T Test is used to determine whether there is an average difference between two unpaired samples (p-value <0.05). Independent sample test results obtained Asymp sig values. (2-tailed) of 0.008 for differences in protein consumption, it was concluded that the difference in protein consumption in adolescent girls who experienced SEZs aged 15-19 years in coastal and non-coastal areas.